Evasão escolar na educação de jovens e adultos: um estudo na EMEF Castelinho do Pequeno Príncipe - SOUZA, Rosalvo Rocha de (2021)
This paper deals with the reality of Youth and Adult Education in the municipality of Novo Repartimento, specifically on school dropouts at the Castelinho do Pequeno Príncipe Municipal School of Elementary Education. From theoretical reference and field research, the causes of school dropout were described and analyzed, a problem that affects most Brazilian schools, revealing a serious picture of public education. The results of the survey, obtained through questionnaires, revealed that in the years 2015 and 2016, the percentage of school dropout reached 55% and 45%, respectively. The factors that contributed to this situation were the most diverse, among which, according to teachers and students, physical fatigue, pregnancy, uninteresting classes and health problems.